Restriction times on the rise: mechanistic modelling of activity time of grassland vipers (Vipera spp.) in the face of climate change - Edvárd Mizsei; Tibor Sos; Attila Móré; Bálint Wenner; Gergő Rák; Konrad Mebert (Frontiers in Zoology, 2025)
Abstract Climate change threatens species adapted to cool alpine environments, particularly ectotherms like reptiles. Small-sized grassland specialist vipers inhabit such environments in Eurasia and are highly susceptible to overheating and dehydration as global temperature rises. This study modelled activity restriction times, defined as hours when environmental temperatures exceed the thermal tolerance (i.e. not available for essential activities) of the species, for 20 grassland viper taxa to assess climate change impacts. Under future conditions, hours of activity restriction are projected to increase by 21% by the SSP1-2.6 scenario, and by 52.1% by the SSP5-8.5 scenario. Elevation and latitude significantly influenced restriction time changes, with high-altitude and northern populations predicted to be most affected. The taxa Vipera graeca and Vipera ursinii moldavica are expected to experience the greatest increase in restriction times. Despite warmer conditions potentially increasing hours within preferred thermal ranges, vipers are unlikely to exploit lower-elevation habitats due to competition and ecological constraints. These findings emphasise the urgent need for conservation strategies, including habitat preservation and connectivity, to mitigate the adverse effects of climate change on grassland vipers, particularly the most vulnerable populations.